Donor Agenda conditionalities and cultural sustainability in Africa the case of Zimbabwe - Mpofu, Philip (Deutschland Lambert Academic Publishing, 2009)
This book discusses the debates on the agenda and conditionalities of donor agencies which are usually subsumed under euphemisms of development, good governance, democracy, rule of law and women/children?s rights among many others. It takes a cultural dimension to this debate as it valorizes self-determination which is premised on cultural freedom and autonomy of the recipient communities in Zimbabwe. The intermittent closures of donor agencies by the Zimbabwean government in the post 2000 period and the continued uproar in the societies on the agenda of some of the donor agencies illustrates the challenges posed by external influences on supposedly autonomous domestic policy adecision making by the indigenous people. Indicative of this, is the uncelebrated agenda and conditionalities which usually manifest in form of prescriptive development paradigms by the donor agencies which are scattered through out the country. The agenda of these donor agencies and the subsequent activities are misdirected mainly because they do not take into account the role of cultural capital and cultural sustainability in sustainable development in the political, economic and socio-cultural spheres
Includes index
Keywords: Donors